Fast-Track Legislation Yang Benar Dan Demokratis - Fadli, Mohammad; Putra, Marsudi Dedi; Sholehudin, Miftahus (Universitas Brawijaya, 2023)
The complexity of social issues is growing in line with the growing modern technology these days, which is disproportionate to its interrupted regulation in the law concerned. Using a comparative and conceptual approach, this article seeks to discuss under what circumstances this fast-track legislation can be implemented and how fast-track legislation should be correctly and democratically implemented. The results show that, fast-track legislation must apply under certain circumstances and be selected, thereby not applying to all bills, and the law-making stages should not be reduced. Second, fast-track legislation must take into account democratic principles in the legislation, or it must comply with procedures, participation, public access, or transparency. Such particular circumstances require simplification of particular stages, while the essence of the democratically-formed legislation must remain.